The effects of media narratives on national identity cards system strategies of Malawi - Frank Makoza (ZBW - Leibniz Information Centre for Economics, 2023)
This paper presents an analysis of how online media narratives shaped national identity cards system strategies. The case of Malawi was analysed as an example of an African country that recently implemented a national identity cards system. The study used Narratives Theory to analyse how narratives presented in government policies, legal documents, and online media reports influenced the implementation of the national identity cards system. The results showed that the events involving illegal immigrants, child trafficking, access to public health services, and challenges with voter registration influenced the implementation of the national identity cards system. Contextual conditions, including lack of financial resources, porous borders, culture, no-fee services in public health facilities, and the absence of a computerised identification system gave rise to the events. Lack of financial resources and focus on other government priorities delayed the implementation of national identity cards systems. The study contributed towards literature on national identity cards systems in the context of Africa.
Keywords: 330; National identity cards systems; Narratives Theory; Online media; Malawi